Three Electrode Cell Assembly for Voltammetric Measurements in Non-Aqueous Solvents - Balasubramanian, S. (Asian Journal of Chemistry, 2010)
The present study describes the construction and use of three electrode cell assembly for voltammetric measurements in nonaqueous media. This cell offers several advantages like ease of handling, low volume of the sample solution, besides offering minimum junction potential.